Haploinsufficiency of the FOXA2 associated with a complex clinical phenotype. Issue 6 (11th April 2020) - Mohammed, Idris; Al‐Khawaga, Sara; Bohanna, David; Shabani, Abdusamea; Khan, Faiyaz; Love, Donald R.; Nawaz, Zafar; Hussain, Khalid
Abstract: Background: There are few reports describing the proximal deletions of the short arm of chromosome 20, making it difficult to predict the likely consequences of these deletions. Most previously reported cases have described the association of 20p11.2 deletions with Alagille syndrome, while there are others that include phenotypes such as panhypopituitarism, craniofacial dysmorphism, polysplenia, autism, and Hirschsprung disease. Methods: Molecular karyotyping, cytogenetics, and DNA sequencing were undertaken in a child to study the genetic basis of a complex phenotype consisting of craniofacial dysmorphism, ocular abnormalities, ectopic inguinal testes, polysplenia, growth hormone deficiency, central hypothyroidism, and gastrointestinal system anomalies. Results: We report the smallest described de novo proximal 20p11.2 deletion, which deletes only the FOXA2 leading to the above complex phenotype. Conclusions: Haploinsufficiency of the FOXA2 only gene is associated with a multisystem disorder. Abstract : Haploinsufficiency of the FOXA2 leads to a complex phenotype consisting of craniofacial dysmorphism, ocular abnormalities, ectopic inguinal testes, polysplenia, growth hormone deficiency, central hypothyroidism, and gastrointestinal system anomalies.